Cost-benefit analysis: Newborn screening for inborn errors of metabolism in Lebanon. (December 2015) - Khneisser, I; Adib, S; Assaad, S; Megarbane, A; Karam, P
Objectives: Few countries in the Middle East-North Africa region have adopted national newborn screening for inborn errors of metabolism by tandem mass spectrometry (MS/MS). We aimed to evaluate the cost-benefit of newborn screening for such disorders in Lebanon, as a model for other developing countries in the region. Methods: Average costs of expected care for inborn errors of metabolism cases as a group, between ages 0 and 18, early and late diagnosed, were calculated from 2007 to 2013. The monetary value of early detection using MS/MS was compared with that of clinical "late detection", including cost of diagnosis and hospitalizations. Results: During this period, 126000 newborns were screened. Incidence of detected cases was 1/1482, which can be explained by high consanguinity rates in Lebanon. A reduction by half of direct cost of care, reaching on average 31, 631 USD per detected case was shown. This difference more than covers the expense of starting a newborn screening programme. Conclusion: Although this model does not take into consideration the indirect benefits of the better quality of life of those screened early, it can be argued that direct and indirect costs saved through early detection of these disorders are important enough to justify universal publicly-funded screening, especially in developing countries with high consanguinity rates, as shown through this data from Lebanon.